Lung Transplant Center Volume Ameliorates Adverse Influence of Prolonged Ischemic Time on Mortality. Issue 1 (13th July 2016) - Hayes, D.; Hartwig, M. G.; Tobias, J. D.; Tumin, D.
Abstract : The influence of prolonged ischemic time on outcomes after lung transplant is controversial, but no research has investigated ischemic time in the context of center volume. We used data from the United Network for Organ Sharing to estimate the influence of ischemic time on patient survival conditional on center volume in the post–lung allocation score era (2005–2015). The analytic sample included 14 877 adult lung transplant recipients, of whom 12 447 were included in multivariable survival analysis. Patient survival was improved in high‐volume centers compared with low‐volume centers (log‐rank test p = 0.001), although mean ischemic times were longer at high‐volume centers (5.16 ± 1.70 h vs. 4.83 ± 1.63 h, p < 0.001). Multivariable Cox proportional hazards regression stratified by transplant center found an adverse influence of longer ischemic time at low‐volume centers but not at high‐volume centers. At centers performing 50 transplants in the period 2005–2015, for example, 8 versus 6 h of ischemia were associated with an 18.9% (95% confidence interval 6.5–32.7%; p < 0.001) greater mortality hazard, whereas at centers performing 350 transplants in this period, no differences in survival by ischemic time were predicted. Despite longer mean ischemic time at high‐volume transplant centers, these centers had favorable patient outcomes and no adverse survival implications of prolonged ischemia. Abstract : This study analyzes national registry data to demonstrate an association between prolonged ischemia of lung allografts and increased post–lung transplant mortality at centers with low procedural volume, but not at high‐ volume centers.